Factors Related to Conservative Preterm Therapy on BPJS Claim Achievement in Waluyo Jati Hospital Probolinggo Regency - Rahmawati, Yessi; Prasetyo, Joko; Wardani, Ratna (Asian Journal of Health Research, 2023)
Introduction: A high number of reports of preterm incidents in Probolinggo, which was the highest in East Java in 2018, has caused problems in the financing process claimed by the Indonesian National Social Health Insurance (Badan Penyelenggara Jaminan Sosial (BPJS)). Insufficient financing for maternity mothers, as the highest proportion of national delivery methods, can certainly be a direct or indirect obstacle to the maternal mortality rate, which is still very high in Indonesia. This research aims to analyze the influence of hospitalization period, gestational age, and delivery method in conservative preterm therapy on BPJS claim achievement at Waluyo Jati Hospital, Probolinggo Regency. Material and Methods: This study is a quantitative research with a cross-sectional approach. Sampling took place from May to September 2023 at Waluyo Jati Regional Hospital, Probolinggo Regency. Sampling used an accidental sampling technique. 33 respondents participated in this research. Results: The results of this study showed that the largest number of respondents with the criteria for a length of stay of 4-7 days was 23 respondents (69.6%), gestation age 31-33 weeks was 14 respondents (42.4%), and 23 respondents underwent cesarean section delivery (69.7%). The highest BPJS claim achievement value was in the range of 30-50%, with 18 respondents (54.5%). The results of the Multiple Linear Regression showed a p-value of 0.000. Conclusion: The conclusion from this research is that there is an influence of hospitalization period, gestational age, and delivery method simultaneously in conservative preterm therapy on the achievement of BPJS claims at Waluyo Jati Hospital, Probolinggo Regency.